Prognostic impact of IKZF1 deletion in adults with common B-cell acute lymphoblastic leukemia. Issue 1 (December 2016) - Yao, Qiu-Mei; Liu, Kai-Yan; Gale, Robert; Jiang, Bin; Liu, Yan-Rong; Jiang, Qian; Jiang, Hao; Zhang, Xiao-Hui; Zhang, Mei-Jie; Chen, Shan-Shan; Huang, Xiao-Jun; Xu, Lan-Ping; et al.
Abstract Background Interrogate the impact ofIKZF1 deletion on therapy-outcomes of adults with common B-cell acute lymphoblastic leukemia. Methods One hundred sixty-five consecutive adults with common B-cell ALL were tested forIKZF1 deletion and for BCR/ABL. Deletions inIKZF1 were detected using multiplex RQ-PCR, multiplex fluorescent PCR, sequence analysis and multiplex ligation-dependent probe amplification (MLPA).BCR/ABL was detected using RQ-PCR. All subjects received chemotherapy and some also received an allotransplant and tyrosine kinase-inhibitors. Multivariate analyses were done to identify associations betweenIKZF1 deletion and other variables on non-relapse mortality (NRM), cumulative incidence of relapse (CIR), leukemia-free survival (LFS) and survival. Results Amongst subjects achieving complete remission those withIKZF1 deletion had similar 5-year non-relapse mortality (NRM) (11 % [2–20 %] vs. 16 % [4–28 %];P = 0.736), a higher 5-year cumulative incidence of relapse (CIR) (55 % [35–76 %] vs. 25 % [12–38 %];P = 0.004), and worse 5-year leukemia-free survival (LFS) (33 % [16–52 %] vs. 59 % [42–73 %];P = 0.012) and survival (48 % [33–62 %] vs. 75 % [57–86 %];P = 0.002). In multivariate analysesIKZF1 deletion was associated with an increased relapse (relative risk [RR] =2.7, [1.4–5.2];P = 0.002), a higher risk of treatment-failure (inverse of LFS;RR = 2.1, [1.2–3.6];P = 0.007) and a higher risk of death (RR = 2.8, [1.5–5.5];P = 0.002). The adverse impact ofIKZF1 deletion on outcomes was stronger in subjects without vs. withBCR-ABL1 and in subjects receiving chemotherapy-only vs. an allotransplant. Conclusions IKZF1 deletion was independently-associated with a higher relapse risk and worse LFS and survival in adults with common B-cell ALL after adjusting for other prognostic variables and differences in therapies. These data suggestIKZF1 deletion may be a useful prognostic variable in adults with common B-cell ALL, especially in persons withoutBCR-ABL1 and those receiving chemotherapy-only. Transplants appear to overcome the adverse impact ofIKZF1 deletion on therapy-outcomes but confirmation in a randomized study is needed. The trial was registered in 2007 with the Beijing Municipal Government (Beijing Municipal Health Bureau Registration N: 2007–1007).